FRI0444 Riociguat for the Treatment of Raynaud's Phenomenon: A Single-Dose, Double-Blind, Randomized, Placebo-Controlled Cross-Over Study (Digit). (9th June 2015) - Huntgeburth, M.; Kießling, J.; Weimann, G.; Kiepsel, V.; Saleh, S.; Hunzelmann, N.; Rosenkranz, S.
Abstract : Background: Raynaud's phenomenon (RP) is a cold- or stress-triggered digital ischemia caused by vasoconstriction in the digital blood vessels. RP may be primary (idiopathic) or secondary. Secondary RP is usually due to a connective tissue disorder. Medical therapy for RP remains unsatisfactory, with many patients not responding to treatment. Objectives: Here we investigated the safety, efficacy, and pharmacokinetics of riociguat, a soluble guanylate cyclase stimulator, in patients with RP. Methods: Eligible patients had primary RP or secondary RP associated with limited cutaneous scleroderma (SSc), diffuse cutaneous SSc, or SSc overlap syndrome. Additional inclusion criteria included age 18–70 years and symptom duration ≥1 year. Patients were randomized to receive a single oral dose of riociguat 2 mg or placebo. For the primary endpoint, digital blood flow in the right index finger was determined by Laser Speckle Contrast Analysis after 5 minutes of cold water exposure. This procedure was performed at baseline and 2 hours after study drug administration. A patient was considered a responder if placebo-corrected blood flow after cold exposure increased by ≥10% vs baseline at 2 hours after drug intake. The goal of the study was to achieve a response rate of 66%. Results: Twenty valid patients entered the study; 17 (85%) were female and the mean (SD) age was 52 (14) years. The majority of patients had secondary RP, which was associated with diffuse cutaneous SSc in 50% of patients (Table 1 ). In total, 12/20 (60%) patients responded to riociguat treatment (Table 1 ). The highest response rates were observed in patients with primary RP and limited cutaneous SSc. Riociguat Cmax (SD) 2 hours after drug intake was 76 (1.5) μg/ml, which is in the range previously observed in healthy volunteers and patients with pulmonary hypertension. Comparable riociguat Cmax values were observed in responders (81 [1.5] μg/ml) and non-responders (71 [1.6] μg/ml). Adverse events were reported in 5 patients receiving riociguat (headache, n=4; dyspepsia, n=1) and 1 patient receiving placebo (malaise). No serious adverse events were reported. Conclusions: Riociguat was well tolerated in patients with primary and secondary RP, and improved blood flow in 60% of patients under conditions of cold exposure. These data suggest that a multi-dose trial investigating the therapeutic effect of riociguat in primary and secondary RP is warranted. Disclosure of Interest: M. Huntgeburth: None declared, J. Kießling: None declared, G. Weimann Employee of: Bayer Pharma AG, V. Kiepsel Employee of: Contractor for Bayer Pharma AG, S. Saleh Employee of: Bayer Pharma AG, N. Hunzelmann: None declared, S. Rosenkranz Grant/research support from: Actavis, Actelion Pharmaceuticals Ltd, Bayer HealthCare Pharmaceuticals, GlaxoSmithKline, Novartis Corp, Pfizer Inc, and United Therapeutics Corp., Consultant for: Actavis, Actelion Pharmaceuticals Ltd, Bayer HealthCare Pharmaceuticals, GlaxoSmithKline, Eli Lilly and Co, Novartis Corp, Pfizer Inc, and United Therapeutics Corp